PERBEDAAN EFEKTIFITAS RELAKSASI BENSON DAN KOMPRES HANGAT DALAM MENURUNKAN NYERI SENDI LANJUT USIA - Hariyanto, Agus; Ma?rifatul Azizah, Lilik (JURNAL KEPERAWATAN SEHAT, 2015)
Rheumatism are often seen in the elderly is rheumatoid arthritis. Rheumatoid arthritis is characterized by inflammation of the common symptoms of pain. Non-pharmacologic treatment that can be used to cope with the pain are Benson relaxation and warm compress. This research aims to prove the different effect of Benson relaxation and warm compress to change the intensity of joint pain in older adults with rheumatoid arthritis in UPT Panti Werdha Mojopahit Mojokerto. In this research design used is Quasy experiment with the approach pre-test post-test control group design. Sample of 18 people were taken by simple random sampling. 9 people from experimental group was given Benson relaxation and 9 people from control group was given warm compress. Collecting data using a pain scale Bourbonais. Paired T-Test shows that p (0.009) < α (0.05), so Ho is rejected it means there are significant Benson relaxation to change the intensity of joint pain in older adults with rheumatoid arthritis. To test the Independent Sample T-Test shows that p (0.176) > α (0.05), so that Ho is accepted it means the average change in pain intensity in experiment group with the control group was significantly the same. In most of the elderly, pain is an problem that will affect the activities of daily activities and quality of life. Chronic pain management often require psychological interventions for elderly. Benson relaxation techniques are passive relaxation techniques is’nt using muscle tension so it is appropriate to relieve pain, because when the muscle tension will increases pain.Keywords: Benson relaxation, Warm compress, joint pain intensity, elderly